Antecedents and Consequences of Airline Customer Satisfaction - Budi Setyanta (Cita Konsultindo Research Center, 2021)
This study aims to identify the forming factors of customer satisfaction and their consequences on consumer behavior. Samples of 100 were taken based on purposive sampling technique with the criteria of having used air transportation, at least 17 years old, and healthy. Collecting data using a Likert scale questionnaire based on the Google Docs platform. This study indicates that customer satisfaction is influenced by price perceptions, service quality, and trust. Affordable and competitive prices are the building blocks of customer satisfaction. Customers consider fair prices in forming their satisfaction with a product or service. This research indicates that customers consider excellent service that exceeds customer expectations to increase satisfaction. Airlines that are perceived to have adequate capabilities in their operations and have the integrity to provide mutual benefits are important factors in customer satisfaction. Satisfaction is an important predictor of repurchasing air transportation services. Satisfaction shapes behavior to suggest others use air transportation services.